A general reaction mechanism for carbapenem hydrolysis by mononuclear and binuclear metallo-β-lactamases - Lisa, María Natalia (2017)
Carbapenem-resistant Enterobacteriaceae threaten human health, since carbapenems are last resort drugs for infections by such organisms. Metallo-β-lactamases (MβLs) are the main mechanism of resistance against carbapenems. Clinically approved inhibitors of MBLs are currently unavailable as design has been limited by the incomplete knowledge of their mechanism. Here, we report a biochemical and biophysical study of carbapenem hydrolysis by the B1 enzymes NDM-1 and BcII in the bi-Zn(II) form, the mono-Zn(II) B2 Sfh-I and the mono-Zn(II) B3 GOB-18. These MβLs hydrolyse carbapenems via a similar mechanism, with accumulation of the same anionic intermediates. We characterize the Michaelis complex formed by mono-Zn(II) enzymes, and we identify all intermediate species, enabling us to propose a chemical mechanism for mono and binuclear MβLs. This common mechanism open avenues for rationally designed inhibitors of all MβLs, notwithstanding the profound differences between these enzymes' active site structure, β-lactam specificity and metal content.